Microbiota promotes recruitment and pro-inflammatory response of caecal macrophages during E. tenella infection - F. Tomal; A. Sausset; Y. Le Vern; L. Sedano; C. Techer; S. Lacroix-Lamandé; F. Laurent; A. Silvestre; F. I. Bussière (Gut Pathogens, 2023)
Abstract Background Eimeria genus belongs to the apicomplexan parasite phylum and is responsible for coccidiosis, an intestinal disease with a major economic impact on poultry production. Eimeria tenella is one of the most virulent species in chickens. In a previous study, we showed a negative impact of caecal microbiota on the physiopathology of this infection. However, the mechanism by which microbiota leads to the physiopathology remained undetermined. Macrophages play a key role in inflammatory processes and their interaction with the microbiota during E. tenella infection have never been investigated. We therefore examined the impact of microbiota on macrophages during E. tenella infection. Macrophages were monitored in caecal tissues by immunofluorescence staining with KUL01 antibody in non-infected and infected germ-free and conventional chickens. Caecal cells were isolated, stained, analyzed and sorted to examine their gene expression using high-throughput qPCR. Results We demonstrated that microbiota was essential for caecal macrophage recruitment in E. tenella infection. Furthermore, microbiota promoted a pro-inflammatory transcriptomic profile of macrophages characterized by increased gene expression of NOS2, ACOD1, PTGS2, TNFα, IL1β, IL6, IL8L1, IL8L2 and CCL20 in infected chickens. Administration of caecal microbiota from conventional chickens to germ-free infected chickens partially restored macrophage recruitment and response. Conclusions Taken together, these results suggest that the microbiota enhances the physiopathology of this infection through macrophage recruitment and activation. Consequently, strategies involving modulation of the gut microbiota may lead to attenuation of the macrophage-mediated inflammatory response, thereby limiting the negative clinical outcome of the disease.